OXPath-based data acquisition for dblp - Michels, C; Fayzrakhmanov, R; Ley, M; Sallinger, E; Schenkel, R (IEEE, 2017)
We demonstrate how the contemporary problems of data acquisi- tion for dblp can be tackled with OXPath. It enables web data ex- traction and wrapper maintenance for heterogeneous data sources on a simple, declarative level. Its features render it a feasible instru- ment to retrieve the varying and changing web representations of the prototypical substructures in the bibliographic domain.